Is “Allah Just for Muslims”?: Religion, Indigenisation and Boundaries in Malaysia - Leong, Susan (2016)
On 2 January 2014, members of the Selangor Islamic Affairs Department (JAIS Jabatan Agama Islam Selangor) confiscated 321 Malay-and Ibanlanguage Bibles from the premises of the Bible Society of Malaysia (Gomez 2014). The raid follows on from the Court of Appeal ruling a few months earlier in October 2013 that the ‘usage of the word Allah is not integral to the Christian faith’ (Anbalagan 2014). It was reasoned that allowing the use of ‘Allah’ to denote God in the Bahasa Malaysia (Malay) section of the Catholic publication,Herald, would ‘cause confusion in the community’, and the court upheld the home...